Substance and shadow of formamidinium lead triiodide based solar cells. Issue 15 (7th April 2021) - Haris, Muhammed P. U.; Kazim, Samrana; Pegu, Meenakshi; Deepa, M.; Ahmad, Shahzada
Abstract : We shed light on the compositional, surface engineering and crystallization kinetics manipulations for FAPbI3 followed by a proposition for unified testing protocols in order to scale-up the solar cells from the lab to the market. Abstract : The current decade has witnessed a surge of progress in the investigation of methyl ammonium lead iodide (MAPbI3 ) perovskites for solar cell fabrication due to their intriguing electro-optical properties, despite the intrinsic degradation of the material that has restricted its commercialisation. As a promising alternative, solar cells based on its formamidinium analogue, FAPbI3, are currently being actively pursued for having demonstrated a certified efficiency of 24.4%, while the room-temperature conversion to a non-perovskite δ-phase impedes its further commercialisation, and strategies have been adopted to overcome this phase instability. An in-depth and real-time understanding of microstructural relationships with optoelectronic properties and their underlying mechanisms using operando in situ spectroscopic techniques is paramount. Thus, the design and development of a new process, data driven methodology, characterization and evaluation protocols for perovskite absorber layers and the fabricated devices is a judicious research direction. Here, in this perspective, we shed light on the compositional, surface engineering and crystallization kinetics manipulations for FAPbI3, followed by a proposition for unified testing protocols, for scalling of devices from the lab to the market.